2021
DOI: 10.1017/jwe.2021.19
|View full text |Cite
|
Sign up to set email alerts
|

Did Wine Consumption Change During the COVID-19 Lockdown in France, Italy, Spain, and Portugal?

Abstract: This article documents how the COVID-19 crisis has affected the drinking behavior of Latin European wine consumers. Using a large online survey conducted during the first lockdown in France, Italy, Portugal, and Spain (n = 7,324 individuals), we reconstruct the purchasing and consumption patterns of the respondents. The number of people who maintained their wine consumption frequency is significantly higher than those who increased or decreased their consumption. Wine consumption frequency held up better than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Dubois et al (2021) studied the behavior of Latin European wine consumers for France, Italy, Portugal and Spain during the first lockdown (sample of 7,324 individuals). They observed that the number of people who maintained their wine consumption frequency is significantly higher than those who increased or decreased their consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dubois et al (2021) studied the behavior of Latin European wine consumers for France, Italy, Portugal and Spain during the first lockdown (sample of 7,324 individuals). They observed that the number of people who maintained their wine consumption frequency is significantly higher than those who increased or decreased their consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is probably because they are not in contact with the final consumer as are those who sell their bottled wines directly to the distribution channels affected by the various lockdown and social‐distancing restrictions. Basic (i.e., entry‐level) wines are the ones that sold best during the lockdowns, especially in Europe (Dubois et al, 2021 ). They tend to be sold mainly in supermarkets, where bag‐in‐box sales have taken an important market share.…”
Section: Regression Analysismentioning
confidence: 99%
“…A series of studies conducted by Wine Intelligence ( 2020 ) revealed that the wines sold are no longer the same. In particular, entry‐level and mid‐range wines or bag‐in‐box wines are preferred by consumers (Rebelo et al, 2021 ; Dubois et al, 2021 ). While these issues, related to consumption and sales, have been widely documented, the academic literature is almost nonexistent in respect of the consequences for wineries.…”
Section: Introductionmentioning
confidence: 99%
“…Agnoli and Charters (2022), showed the differences between wine and alcohol consumption, and the consumption of aesthetic, quasi-aesthetic and serious leisure products more widely, and that is the necessity of examining differences between professional and non-professional consumers. Dubois, Agnoli, Cardebat, Compés, Faye, Frick, and Simon-Elorz (2021), present how that the COVID-19 crisis has affected the drinking behavior of Latin European wine consumers. Wine consumption frequency held up better than other types of alcohol (beer and spirits).…”
Section: Theoretical Framework and Previous Studiesmentioning
confidence: 99%
“…In 2019 and 2020, weather conditions were favorable, but the COVID-19 pandemic forced winemakers from key wine-producing countries (France and Spain) to reduce yields to avoid overproduction (Wittwer and Anderson, 2021). In addition, the pandemic also affected the decline in trade (Agnoli and Charters, 2022;Dubois, Agnoli, Cardebat, Compés, Faye, Frick, and Simon-Elorz, 2021), losses from travel and tourism, which is one of the key factors influencing the development and sale of products (Gutsalenko, Marchuk, Hutsalenko, and Tsaruk, 2020).…”
Section: Economic Situationmentioning
confidence: 99%